2021
DOI: 10.3390/plants10102076
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Increased Temperatures and High Irradiation Causes Changes in Photosynthetic Efficiency

Abstract: Global warming and the associated climate change are imposing abiotic stress on plants. Abiotic factors are crucial for plant productivity, survival, and reproduction. Eight sunflower hybrids were tested in conditions of different water availability and with combinations of different temperatures and irradiation. The changes in the photosynthetic efficiency were measured in the morning (control conditions: 2013, 25.8 °C and 349.1 W m−2; 2014, 21.8 °C and 296.4 W m−2) and afternoon (the combination of increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…These results, coupled with the decrease in the fully active RC combined with the increase in heat sink dissipation centres, clearly indicate PS II down-regulation and the potential induction of a photoinhibition state [60]. An overview of the PGPR effects can be seen by analysing the performance index, known for being a sensitive indicator of heat stress that relates energy absorption, antenna steps, reaction centre and electron transport chain functioning [61,62]. As estimated previously, a significantly HW-reduced performance index in the non-inoculated plants was observed when compared to C2-inoculated individuals, which exhibited a performance index increase under heatwave conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These results, coupled with the decrease in the fully active RC combined with the increase in heat sink dissipation centres, clearly indicate PS II down-regulation and the potential induction of a photoinhibition state [60]. An overview of the PGPR effects can be seen by analysing the performance index, known for being a sensitive indicator of heat stress that relates energy absorption, antenna steps, reaction centre and electron transport chain functioning [61,62]. As estimated previously, a significantly HW-reduced performance index in the non-inoculated plants was observed when compared to C2-inoculated individuals, which exhibited a performance index increase under heatwave conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Effective and precise irrigation is a challenging task due to spatial and temporal variation in meteorological and soil conditions (Ferentinos et al, 2017; Nebbali et al, 2012). Plants respond to these conditions instantaneously, by managing their water balance to optimize their productivity–survivability ratio (Markulj Kulundži et al, 2021). For example, adjustment of stomatal opening serves as a key physiological trait, optimizing the plant response by controlling the influx of CO 2 and H 2 0, to support photosynthesis and transpiration, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the ChlF method on sunflowers started immediately after its introduction [7,8]. Some of the resulting research on sunflower deal with the photosynthetic characteristics at different nitrogen inputs into the soil [9], differences under combined salt and drought stress [10], the impact of light and heat stress on sunflower genotypes [11,12], the effect of drought and heat stress on sunflower [13] and by examining the effects of other environmental stresses on sunflower plants.…”
Section: Introductionmentioning
confidence: 99%
“…The sunflower plant's potential was manifested by higher tissue permeability for CO 2 diffusion and high RuBisCO activity, which resulted from stomata on both sides of the leaf [30]. Furthermore, studying the behavior of ChlF parameters by stages of sunflower development, it was observed that the values of photosynthetic parameters depend on the sunflower development stage [31].…”
Section: Introductionmentioning
confidence: 99%